Extractive spectrophotometric methods for determination of ciprofloxacin in pharmaceutical formulations using sulfonephthalein acid dyes - Dung, Nguyen Trung; Bau, Le Hoc; Thao, Le Quang; Dat, Nguyen Dang (Vietnam Journal of Chemistry, 2017)
Three simple, rapid, sensitive and accurate extractive-spectrophotometric method for the determination of ciprofloxacin in pharmaceutical preparation has been developed. These methods are based on the formation of yellow ion-pair complexes between the examined drug and three sulfonephthalein acid dyes, namely; bromophenol blue (BPB), bromocresol green (BCG), and bromothymol blue (BTB) in acidic medium. The formed complexes were extracted with chloroform and measured at 420, the colored chromogen was stable for twenty four hours. The effect of optimum conditions via pH, dye concentration, time and solvent are studied. Beer’s law is obeyed in the concentration ranges 0.50-25.0 μg/mL with molar absorptivity of 1.46´104, 1.83´104 and 2.07´104 L. mol-1. cm-1 and limit of detection (LOD) of 0.105, 0.101, 0.084 for BPB, BCG and BTB methods, respectively. No interference was observed from common excipients present in pharmaceutical formulations. The proposed method has been applied successfully to determine ciprofloxacin in pharmaceutical preparation (tablets, infusion and eye drops). Keywords. Ciprofloxacin, extraction-spectrophotometry, ion pair complex; sulfonephthalein dyes.